Vehicle Trade of Defaulted Finance Lease Companies in Mataram City Sharia Economic Perspective - Hidayanti, Nur Fitri; Hulaimi, Ahmad; Ariani, Zaenafi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In Indonesia, auctions were officially entered in 1908 with the Auction Law, Vendu Reglement, in Staatblad 1908 Number 189. Public sales or auctions are any sale of goods in public by oral and/or written bidding efforts to gather interested parties/auction participants. Vehicle auctions for defaulted owners who can no longer make payments will proceed with auctioning the vehicle. Auction sales in fiqh muamalah are called Bai' imuzayyadah or more commonly known as auction sales, which is a form of offering merchandise in a crowd where buyers bid with higher prices until the highest price is reached, and a contract is made, and the buyer takes the goods from the seller. The purpose of this study is to thoroughly explore the auction sale process of defaulted vehicles by finance companies in Mataram City. The method used in this research is qualitative, with key informants being debt collectors, both freelance and permanent employees from PT. Adira Dinamika Multi Finance Syariah Tbk Mataram branch. The study results show that the entire auction sale process has complied with the applicable regulations and follows Islamic Sharia.